Lifetime injury prevention: The sport profile model* - Webborn, N (South African Journal of Sports Medicine, 2012)
Participation in sporting activities carries an injury risk. Conversely, the increased awareness that physical inactivity is a major risk factor for disease has led government agencies and the medical community to encourage increased levels of physical activity. Many people will achieve this through participation in sport. Injury inevitably leads to a reduction in participation on a temporary or permanent basis, but the injury experience may also influence the lifelong physical activity behaviour. Few studies adequately examine the possible long-term consequences of sport participation after the competitive period has been completed, but by understanding the patterns of injuries in different sports one test can develop strategies to prevent and better manage the conditions that occur and promote lifelong physical activity. There is a need to develop models of understanding of injury risk at different life phases and levels of participation in a specific sport. The risk assessment of sport participation has to be relevant to a particular sport, the level of participation, skill, age and potential future health consequences. This article describes a sport-specific model which will improve guidance for coaches and healthcare professionals. It poses questions for sports physicians, healthcare providers, educators and for governing bodies of sports to address in a systematic fashion. Additionally the governing body, as an employer, will need to meet the requirements for risk assessment for professional sport and its ethical responsibility to the athlete.